A Comparative Approach of Japanese Project Management in Construction, Manufacturing and IT Industries - Low, F.S.; Chong, Heap Yih (Elsevier, 2012)
An effective project management approach is key to obtaining successful projects. In this study, a review of the three main industries that practise project management is conducted. This paper focusses on the application of Japanese project management (JPM) methods, namely Project and Program Management (P2M)/Kaikaku Project Management (KPM) in construction, manufacturing and information technology (IT) industries. KPM evolves from P2M, and KPM’s 3K- kakusin (innovation), kaihatsu (development) and kaizen (improvement) are the essences applied when practicing JPM style. In conclusion, the nature of practice in these three industries is different, but the management methods and approaches are almost the same.